Answers

2016-07-03T00:02:28+08:00
   let take the equation     x² + 6x - 7 =  0
    first step transfer the #  7  to the right side
     so we    x² + 6x  =    7
     then divide six by 2 and squared it    that is     (6/2)²  = 9
     now we have   x² + 6x + 9  =   7+ 9  / since we added 9 to the left we                                                                        must also add 9 to the right side
complete the square  (x+3)²  =16
                                   x + 3  = +  or - √16   =    4  or - 4
                                    x  =   4-3  =  1   or   -4 -3  =   -7
1 5 1
  • Brainly User
2016-07-03T00:36:12+08:00
Solving Quadratic Equation by Completing the Square:

a x^{2}  + bx + (  \frac{b}{2}) ^{2}  = c + (  \frac{b}{2}) ^{2}

Please click image below to view more complex example with solution.

Also, please note that the answer of other user here, cheajimmy, is completely correct, so consider the example he posted (a less complex equation).
0